The behavior of a magnetized plasma under the action of laser with high pulse energy - Ryzhkov, S.V. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Simple magnetic traps, such as a cusp and field-reversed configuration are considered for application in high density regime. Magneto-inertial fusion with laser compression of magnetized spherical target and features of laser driven magneto-inertial fusion (LDMIF) are presented. A new fusion scheme which can avoid some of the major difficulties faced in the present approaches in magnetic and inertial confinement fusion is shown. Different schemes of magnetized discharges for LDMIF are discussed. Contributions (fusion power, charged particles and neutrons deposition, thermal conduction, radiation and mechanical work) to a power balance of compressed plasma target are calculated. Рассмотрен магнитно-инерциальный термоядерный синтез с лазерным драйвером. Представлено моделирование сильно нелинейного режима взаимодействия мощного лазерного импульса с предварительно замагниченной плазмой. В качестве мишеней выбраны магнитные системы удержания плазмы антипробкотрон (касп) и компактный тор (обращенная магнитная конфигурация). Обсуждаются вопросы самосогласованного и внешнего приложенного магнитного поля. Проведен анализ энергетического баланса D-T-плазмы при сферически симметричной имплозии мишени лазером с высокой энергией импульса. Получены основные энергетические характеристики плазменной мишени, вмороженной в магнитное поле. Розглянуто магнітно-інерціальний термоядерний синтез з лазерним драйвером. Представлено моделювання сильно нелінійного режиму взаємодії потужного лазерного імпульсу з попередньо замагніченною плазмою. В якості мішеней вибрано магнітні системи утримання плазми антіпробкотрон (асп) і компактний тор (звернена магнітна конфігурація). Обговорюються питання самоузгодженого і зовнішнього прикладеного магнітного поля. Проведено аналіз енергетичного балансу D-T-плазми при сферично симетричній імплозії мішені лазером з високою енергією імпульсу. Отримано основні енергетичні характеристики плазмової мішені, вмороженої в магнітне поле.